2016
DOI: 10.18632/oncotarget.8861
|View full text |Cite
|
Sign up to set email alerts
|

NLRX1 suppresses tumorigenesis and attenuates histiocytic sarcoma through the negative regulation of NF-λB signaling

Abstract: Histiocytic sarcoma is an uncommon malignancy in both humans and veterinary species. Research exploring the pathogenesis of this disease is scarce; thus, diagnostic and therapeutic options for patients are limited. Recent publications have suggested a role for the NLR, NLRX1, in acting as a tumor suppressor. Based on these prior findings, we hypothesized that NLRX1 would function to inhibit tumorigenesis and thus the development of histiocytic sarcoma. To test this, we utilized Nlrx1−/− mice and a model of ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…Prior studies evaluating NLRX1 in cancer have found a role for NLRX1 in the regulation of macrophage proliferation (11). Specifically, macrophages harvested from Nlrx1 −/− mice demonstrated a significant increase in proliferation under specific physiological conditions (11).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies evaluating NLRX1 in cancer have found a role for NLRX1 in the regulation of macrophage proliferation (11). Specifically, macrophages harvested from Nlrx1 −/− mice demonstrated a significant increase in proliferation under specific physiological conditions (11).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, macrophages harvested from Nlrx1 −/− mice demonstrated a significant increase in proliferation under specific physiological conditions (11). Following TBI, microglia in the lesion area undergo proliferation in response to injury and play vital roles in both the modulation of secondary injury and recovery (26, 27).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations